Five-year change in maximum tongue pressure and physical function in community-dwelling elderly adults - Chiaki Higa; Takahiro Mori; Aya Hiraoka; Chiho Takeda; Azusa Kuroki; Mineka Yoshikawa; Mitsuyoshi Yoshida; Kazuhiro Tsuga (Elsevier, 2020)
Background/purpose: To identify age-related changes in maximum tongue pressure (MTP), it is necessary to determine individual biological age. The fitness age score (FAS) is used to calculate the biological age, based on the one-leg standing time with eyes open, vertical jump height, grip strength, functional reach, and 10-m walk time. Materials and methods: The study included 112 community-dwelling elderly adults (42 males and 70 females). We investigated MTP, FAS, and body mass index (BMI) at baseline and 5 years later. MTP was determined with a pressure measurement device. Results: A significant reduction in MTP, FAS, and BMI in both male and female subjects was observed at 5 years. A negative correlation between change in MTP and baseline MTP was observed, but there was no correlation between MTP change and baseline FAS, BMI, and change in FAS and BMI. Conclusion: Age-related decline in MTP might be associated with high MTP, reflecting decreased reserve. Additionally, age-related decline in tongue function might be different from that of physical function.